Comparative Study of Indonesian and Malaysian Civil Service Reform - Tria Noviani Suhendar; Reza Fathurrahman (Journal of Social Research, 2023)
Public service reform has demanded personnel reform to ensure that public services are carried out effectively. The success of personnel reform then needs to be assessed to know how far it has worked in a country to find out how effectively the reform effort has been implemented. This paper aims to conduct a comparative review of the extent to which personnel reform has been implemented in Indonesia and Malaysia. This research was conducted by qualitative method with a comparative study approach. Secondary data were used in the study by taking from databases provided by the United Nations and the World Justice Project. The comparison was carried out using five indices, namely E-government development index (EGDI), E-Participation Index (EPI), Rule of Law Index, Corruption Perceptions Index (CPI), and Democracy Index. In addition, secondary data are also obtained from literature studies of books, research journals, and other sources that are in accordance with the research problem. The results showed that overall Malaysia is superior in the successful implementation of personnel reform when compared to Indonesia in terms of implementing e-government and ensuring its public services are delivered accountably. However, in involving public participation in e-government operators, Indonesia is superior when compared to Malaysia. The implication of the research for the Indonesian government is the demand to better develop its personnel reform policies to ensure more effective and accountable public services in the future.